Exploring the Teacher Empowerment Strategies of School Heads at Secondary Level in Punjab, Pakistan - Zara Khan, Samra Saeed, Afshan Naseem (JCTE, 2023)
Teacher empowerment strategies are essential for a positive organizational identity. School heads are expected to use a variety of empowerment techniques to maximize the potential of their faculty members, inspire them in various ways, and motivate them to work. The current study intends to investigate the teacher empowerment strategies of secondary school heads in Punjab, Pakistan. A study was based on a qualitative research design. The semi-structured interview protocol was used to collect data. A purposive sampling technique was used. The sample was comprised of 57 secondary school teachers. Data were analyzed through the thematic analysis technique. The findings show that school heads have given their staff members greater autonomy by fostering opportunities for group decision-making, praising employees for good work, increasing self- efficacy, and promoting effective teacher collaboration. However, school heads have less focus on professional growth opportunities, supporting teachers' autonomy, and improving their status.